2022
DOI: 10.3390/ijerph19159499
|View full text |Cite
|
Sign up to set email alerts
|

Expectations about the “Natural Order of Things” and Conspiracy Beliefs about COVID-19

Abstract: The COVID-19 pandemic represents an event that unsettled the social and economic life of many people. When individuals are faced with shocking events, they may need to find plausible explanations for such events to restore control and make sense of reality. The adoption of conspiracy beliefs may represent a functional strategy for this purpose. The present study investigated whether the endorsement of conspiracy beliefs may be associated with the degree to which an upsetting event (i.e., the COVID-19 pandemic)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In addition, these study results may be used as basic data for revitalizing clinical practice, community health management, intervention, and research in the future. However, because this study was conducted using an internet-based survey method during the development and validity evaluation process, differences in results and selection bias problems cannot be excluded when factors such as academic background and health status are included [ 41 , 42 ]. In addition, according to previous studies, it is reported that psychological factors such as environment, values, social beliefs, and guilt can affect beliefs, so further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these study results may be used as basic data for revitalizing clinical practice, community health management, intervention, and research in the future. However, because this study was conducted using an internet-based survey method during the development and validity evaluation process, differences in results and selection bias problems cannot be excluded when factors such as academic background and health status are included [ 41 , 42 ]. In addition, according to previous studies, it is reported that psychological factors such as environment, values, social beliefs, and guilt can affect beliefs, so further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 Conspiracy Scale (Giacomantonio et al, 2022): This scale consists of eight items which evaluates people's conspiracy beliefs related to COVID‐19 pandemic. The 5‐point Likert scale was from 1 = totally disagree to 5 = totally agree .…”
Section: Methodsmentioning
confidence: 99%
“…There are several themes that characterize CTs such as the oppositional nature, in the sense that they counter the publicly accepted explanation of an event, the description of a malevolent act, the attribution of agency to powerful persons and groups rather than to systemic effects, the tendency to falsity and the potential to interpret and to shape social events (Biddlestone, Green, et al, 2022; Douglas et al, 2019, 2022; Douglas & Sutton, 2011, 2018; Imhoff et al, 2022; Jolley et al, 2020; Liekefett et al, 2021; Wood & Douglas, 2013). To date, CTs are many and they touch a great number of phenomena and aspects of reality, ranging from health (Giacomantonio et al, 2022) to the environment and climate (Biddlestone, Azevedo, & van der Linden, 2022), from migratory phenomena (Plenta, 2020) to terrorist attacks (Kruglanski et al, 2022), including all the eccentric ones related to aliens, famous deaths, flat earth, the denial of moon landing and so on (Salvati et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the embrace of specific medical-related conspiracies can drive mistrust in health professionals and health institutions, as well as discourage individuals from seeking medical help [ 24 , 25 , 26 , 27 ]. Examples of the negative consequences of conspiratorial ideas on health behavior were manifested during the coronavirus disease 2019 (COVID-19) pandemic and included: lower adherence to following public health preventive measures, including the use of face masks, and reluctance or resistance to get vaccinated, defined as vaccination hesitancy [ 28 , 29 , 30 , 31 , 32 ]. Thus, the harmful effect of vaccination hesitancy extends beyond the mere holding of these beliefs to involve behavior manifested in lower vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%